Digitale tegnologie in die bevordering van vaardigheidsontwikkeling vir leerders met erge intellektuele gestremdheid - Botha, Zelda (Stellenbosch : Stellenbosch University, 2021)
ENGLISH ABSTRACT: Digital technology has become an integral part of everyday life and is increasingly being used to enhance access to and quality of education. In South Africa, the Education White Paper 7 provided an impetus for the Smart-classroom project in which the WCED has equipped special schools with various learning technologies. While there is ample literature on the use of technology in mainstream schools, very limited literature is available on the value of technology in special schools. The central theme of this thesis is therefore the use of digital technology for skills development of learners with severe intellectual disabilities. This study was conducted within the framework of the explanatory-sequential-mixed-method research design with socio-constructivism as the philosophical framework. Data were collected and analysed according to the explanatory-sequential-mixed method. Quantitative data (digital online questionnaire) and qualitative data (group interviews and semi-structured interviews) were collected separately. This data was set against the background of an extensive literature study. The school was purposively selected as one of the pilot schools in the Smart-classroom project of the WCED. The participants were purposively selected to represent teachers and therapists at special schools for learners with severe intellectual disabilities. Aligned with the research design, data analysis was done statistically as well as thematically. Findings were then integrated and thematically discussed. Triangulation was used to verify the reliability and validity of the research findings. Three themes emerged from the findings. The findings indicated that initially, some participants were hesitant to use technology for skills development for learners with severe intellectual disability. However, with regular use, training and support they became more confident. Findings indicate the positive value of digital technology in skills development for learners with severe intellectual disabilities. By mapping the findings from the data against the literature review, the researcher made several recommendations to promote and improve the use of digital technology in special schools with specific reference to learners with severe intellectual disability. In conclusion, as an outflow of this research, the researcher has identified a need and subsequently created an application (app) for developing the packaging skills required within protective (sheltered) labour market environments for learners with severe intellectual disability after completing their school career. This application will be available on the Google Play Store as well as other virtual platforms in the near future.